Potential Utilization of Plastic River Debris as Electricity Power Plant in Jakarta, Indonesia - Mega Mutiara Sari; Takanobu Inoue; Regil Kentaurus Harryes; Kuriko Yokota; Iva Yenis Septiariva; Sapta Suhardono; Ika Bagus Priyambada; Shigeru Kato; Suprihanto Notodarmojo; I Wayan Koko Suryawan (CV. Literasi Indonesia, 2022)
River debris is the main problem from the negative impact of poor waste management. The composition of river debris in Jakarta consists mostly of plastic waste. Plastic waste from river debris has an opportunity for energy recovery. This study aimed to see the potential for utilizing river debris in energy recovery in power plants. This research was conducted at three sampling shelter points in Pesing, Pluit, and Perintis. Waste generation and composition were quantified using the load count method on Indonesian state standards for seven consecutive days. River debris generation in Pesing, Pluitm, and Pernting averaged 7.2; 3; and 1.8 tons/day. More than 60% (w/w) of plastic bag waste was found in the Pesing and Pluit shelters, while 67.3% was found in the Perintis shelter. Based on the calorific value of each plastic waste, the energy potential from plastic waste recovery can reach 16,197,109 kWh/year. This is equivalent to an electricity supply of 0.05% of the total electricity demand in Jakarta.